THE PROFILE ANALYSIS OF SCIENTIFIC LITERACY’ PROSPECTIVE ELEMENTARY TEACHER AS AN INITIAL STRATEGY TO CONDUCT SCIENCE COURSES - Hanifah Mulyani (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Scientific literacy is one of the most important aspect students should have, either for now or in the future. Related to educational challenges of the 21st century, this literacy is actually needed to help students in taking decision when they try to solve any problem in any field, understand all the context of changes that probably occurred in society. According to PISA results in 2022, scientific literacy of students in Indonesia was categorized as low. Educational institutions have responsibilities to improve the quality of education, including students’ scientific literacy. Teachers who have good scientific literacy are expected to offer some contributions in improving students’ scientific literacy as well. This research was conducted to analyze the scientific literacy of prospective elementary teachers. Descriptive qualitative method was used, involving 120 students, called as prospective elementary teachers, as research subjects. The data was taken by giving test of scientific literacy using eight indicators of Gormally. questionnaire of students’ learning history, and interview to some research subjects. Furthermore, the data analysis used in this research was inductive technique using Miles and Huberman Model, consisted of several steps; collecting, reducing, displaying, and verifying data as final steps to the conclusion. The result of this research was scientific literacy of prospective elementary teacher still categorized as moderate since the average score was 47,5 with range score around 27 until 63 in each indicator. This result indicated that the lecturer may consider some learning strategies where science process skill of students could be well-developed, integrate science and mathematics courses, engage students in more scientific reading, and together with institutions provide good maintenance in learning facilities. Keywords: scientific literacy, prospective elementary teacher, science courses